What every endoscopist should know about decontamination - Griffiths, Helen (Frontline Gastroenterol, 2019)
Carbapenemase-resistant Enterobacteriaceae (CRE) has been implicated in an alarming increase in the incidence of endoscopy-associated infections and deaths worldwide. Public Health England acknowledges that the rapid spread of CRE bacteria poses an increasing threat to public health and modern medicine here in the UK. As endoscopists, we assume that the endoscope we are handed has been appropriately decontaminated, but how many of us can honestly say that we understand the process and the pathway by which the instruments we use are reprocessed? Do we understand the associated risks if the pathway fails and our part in supporting the teams responsible for this critical role? Successful decontamination of endoscopes is everyone’s business, and this article outlines what every endoscopist should know about decontamination.